Carbonized shrinkage force of anthracite briquette and large tamped coal cake. (1st December 2019) - Wang, Qi; Zhang, Tiankai; Zhao, Yuqiong; He, Shouqi; Zhang, Yongfa
Graphical abstract: Highlights: Type and definition of anthracite briquette shrinkage force is specified. Formation mechanism of anthracite briquette shrinkage force is explored. Carbonized shrinkage forces of briquette and large coal cake are calculated. Abstract: During high-temperature treatment, shrinkage stress of high-rank coal briquette often leads to crack formation, affecting the particle size distribution of briquette. Thus the type and formation mechanism of anthracite briquette shrinkage force were evaluated. The calculation methods of carbonized shrinkage forces of anthracite briquette and large tamped coal cake (16780 mm * 500 mm * 6630 mm) were also established. The results revealed that carbonized shrinkage of anthracite briquette was affected by four forces: thermal shrinkage force of anthracite coal ( FC ) and binder ( FB ), thermal fusion force ( FF ), and thermal traction force ( FT ). Below 250 °C, FC, FB and FT were derived from capillary pressure and surface tension. FF came from the gravity of softened binder. Between 250 and 750 °C, FC and FB were both originated from resultant force of thermal depolymerization shrinkage force and volatiles precipitation expansion force. FF and FT were provided by co-carbonization products of anthracite coal and binder. Between 750 and 950 °C, FC and FB was induced by resultant force of thermal polycondensation shrinkage force and gas precipitation expansion force. FF acted through catalytic effect of the binder on anthracite and FT no longer provided traction. Four carbonized shrinkage forces of anthracite briquette and tampered coal cake could be calculated according to the equations: F C = K C m Cp d 2 R Cp dt 2, F B = K B m Bp d 2 R Bp dt 2, F F = K B m Bp d 2 R ( C B - F ) p dt 2, F T = K B m Bp d 2 R ( C B - T ) p dt 2, and F cake = y z ∑ i = 1 x ( F C + F B + F F + F T ) i . This study provides guidance for high-rank coal briquette production and stretches the mind for parameter calculations of multi-phase system during chemical reaction.